2009
DOI: 10.1111/j.1467-8527.2009.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Gypsy, Roma and Traveller Children in Schools: Understandings of Community and Safety

Abstract: This paper examines understandings of community and safety for Gypsy, Roma and Traveller (GRT) groups in schools in a metropolitan borough. One school in particular was identified as being the 'Gypsy school' and was attended by the majority of GRT children in the borough. The school was recognised as a model of 'good practice' reflecting its holistic approach towards the GRT community but it was also successful for wider reasons. A picture of the intersection of different communities emerged from interview ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…As noted by Myers and Bhopal (2009) Similarly, isolated accounts of unhappy experiences in secondary school can be transmitted and preserved by community members (see 'scripts' below), acting as a barrier to transfer and retention. In these situations, the re-establishment of safety and trust is a priority but can take time to be restored.…”
Section: Demographic and Community Influencesmentioning
confidence: 99%
“…As noted by Myers and Bhopal (2009) Similarly, isolated accounts of unhappy experiences in secondary school can be transmitted and preserved by community members (see 'scripts' below), acting as a barrier to transfer and retention. In these situations, the re-establishment of safety and trust is a priority but can take time to be restored.…”
Section: Demographic and Community Influencesmentioning
confidence: 99%
“…According to Myers and Bhopal(2009), it was effective to perceived school as a safe place that Romani children were been altogether with the other Romani children. Another result of the research revealed that the level of school satisfaction of Romani children does not differ according to the gender variable.…”
Section: Kaynaklarmentioning
confidence: 99%
“…Above all, building trust with Roma families has proven to be vital to secure school access and achievement (Scullion and Brown 2013;Myers, McGhee and Bhopal 2010;Myers and Bhopal 2009). …”
Section: Locates This Conflict 'In the Opposing Structures Values Anmentioning
confidence: 99%
“…Bhopal 2004;2011;Myers and Bhopal 2009). Active consultation and involvement of parents and children in the educational process shows to be beneficial for improving the educational achievement of these pupils, as well as for reducing drop-out rates (Bhopal 2004).…”
Section: Education In a Broader Societal Contextmentioning
confidence: 99%